Identifying Patterns of Medical Intervention in Acute Respiratory Failure: A Retrospective Observational Study - Jacqueline M. Kruser, MD; Kartikey Sharma, PhD; Jane L. Holl, MD; Omid Nohadani, PhD (Critical Care Explorations, 2023)
IMPORTANCE:. Characterizing medical interventions delivered to ICU patients over time and their relationship to outcomes can help set expectations and inform decisions made by patients, clinicians, and health systems. OBJECTIVES:. To determine whether distinct and clinically relevant pathways of medical intervention can be identified among adult ICU patients with acute respiratory failure. DESIGN, SETTING, AND PARTICIPANTS:. Retrospective observational study using all-payer administrative claims data from 2012 to 2014. Patients were identified from the Healthcare Cost and Utilization Project State Inpatient Databases from Maryland, Massachusetts, Nevada, and Washington. MAIN OUTCOMES AND MEASURES:. Patterns of cumulative medical intervention delivery, over time, using temporal k-means clustering of interventions delivered up to hospital days 0, 5, 10, 20, and up to discharge. RESULTS:. A total of 12,175 admissions were identified and divided into training (75%; n = 9,130) and validation sets (25%; n = 3,045). Without applying a priori classification and using only medical interventions to cluster, we identified three distinct pathways of intervention accounting for 93.5% of training set admissions. We found 45.9% of admissions followed a “cardiac” intervention pathway (e.g., cardiac catheterization, cardioversion); 36.7% followed a “general” pathway (e.g., diagnostic interventions); and 17.4% followed a “prolonged” pathway (e.g., tracheostomy, gastrostomy). Prolonged pathway admissions had longer median hospital length of stay (13 d; interquartile range [IQR], 7.5–18.5 d) compared with cardiac (5; IQR, 2.5–7.5) and general (5; IQR, 3–7). In-hospital death occurred in 24.6% of prolonged pathway admissions compared with 17.9% of cardiac and 6.9% of general. Findings were confirmed in the validation set. CONCLUSIONS AND RELEVANCE:. Most ICU admissions for acute respiratory failure follow one of three clinically relevant pathways of medical intervention which are associated with hospitalization outcomes. This study helps define the longitudinal nature of critical care delivery, which can inform efforts to predict patient outcomes, communicate with patients and their families, and organize critical care resources.